Practical Application of a Bioenergetic Model to Inform Management of a Declining Fur Seal Population and Their Commercially Important Prey - McHuron, Elizabeth A.; Luxa, Katie; Pelland, Noel A.; Holsman, Kirstin; Ream, Rolf; Zeppelin, Tonya; Sterling, Jeremy T. (Frontiers in Marine Science, 2020)
Food availability is a key concern for the conservation of marine top predators, particularly during a time when they face a rapidly changing environment and continued pressure from commercial fishing activities. Northern fur seals (Callorhinus ursinus) breeding on the Pribilof Islands in the eastern Bering Sea have experienced an unexplained population decline since the late-1990s. Dietary overlap with a large U.S. fishery for walleye pollock (Gadus chalcogrammus) in combination with changes in maternal foraging behavior and pup growth has led to the hypothesis that food limitation may be contributing to the population decline. We developed age- and sex-specific bioenergetic models to estimate fur seal energy intake from May - December in six target years, which were combined with diet data to quantify prey consumption. There was considerable sex- and age-specific variation in energy intake because of differences in body size, energetic costs, and behavior; net energy intake was lowest for juveniles (18.9 MJ sea-day-1, 1,409.4 MJ season-1) and highest for adult males (66.0 MJ sea-day-1, 7,651.7 MJ season-1). Population-level prey consumption ranged from 255,232 t (222,159 - 350,755 t), 95% CI) in 2006 to 500,039 t (453,720 - 555,205 t) in 1996, with pollock comprising between 41.4 - 76.5% of this biomass. Interannual variation in size-specific pollock consumption appeared largely driven by the availability of juvenile fish, with up to 81.6% of pollock biomass coming from mature pollock in years of poor age-1 recruitment. Relationships among metabolic rates, trip durations, pup growth rates, and energy intake of lactating females suggest the most feasible mechanism to increase pup growth rates is by increasing foraging efficiency through reductions in maternal foraging effort, which is unlikely to occur without increases in localized prey density. By quantifying year-specific fur seal consumption of pollock, our study provides a pathway to incorporate fur seals into multispecies pollock stock assessment models, which is critical for fur seal and fishery management given they were a significant source of mortality for both juvenile and mature pollock.